Transactions on engineering technologies : International Multiconference of Engineers and Computer Scientists 2016 - Ao, Sio-Iong; Kim, Haeng-Kon; Huang, Xu; Castillo, Oscar (Springer, 2017)
This volume contains selected revised and extended research articles written by prominent researchers who participated in the International MultiConference of Engineers and Computer Scientists 2016, held in Hong Kong, 16-18 March 2016. Topics covered include engineering physics, communications systems, control theory, automation, engineering mathematics, scientific computing, electrical engineering, and industrial applications. The book showcases the tremendous advances in engineering technologies and applications, and also serves as an excellent reference work for researchers and graduate students working on engineering technologies, physical sciences and their applications.
Keywords: Engineering -- Congresses.; Technology -- Congresses.; Computer science -- Congresses.; elektronické knihy; electronic books